2010
DOI: 10.1007/s11738-010-0655-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects and transport of 24-epibrassinolide in heat-stressed barley

Abstract: This paper presents a study of the metabolic response (dark respiration intensity, photosystem II efficiency, metabolic activity) and the yield of barley treated with 24-epibrassinolide and subjected to high-temperature stress. Transport of exogenously applied 24-epibrassinolide in barley and changes in the profile of brassinosteroids that may occur in tissues after 24-epibrassinolide application were also studied. The water solution of 24-epibrassinolide (0.005 and 0.25 mg dm -3 ) was applied via infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…Brassinosteroids are steroidal plant growth promoting regulators, which control complex metabolic pathways in the plants development and vegetative growth (Fridman and SavaldiGoldstain 2013;Holá et al 2010). Brassinosteroids are also very important in the plant's protection against heat stresses, oxidative stress, drought and salinity (Bajguz and Hayat 2009;Janeczko et al 2011;Fahad et al 2015) and may be involved in increasing resistance to biotic stresses by inducing the systemic resistance process (Nakashita et al 2003). At high temperatures, brassinosteroids also affect the plant's carbohydrate metabolism and photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Brassinosteroids are steroidal plant growth promoting regulators, which control complex metabolic pathways in the plants development and vegetative growth (Fridman and SavaldiGoldstain 2013;Holá et al 2010). Brassinosteroids are also very important in the plant's protection against heat stresses, oxidative stress, drought and salinity (Bajguz and Hayat 2009;Janeczko et al 2011;Fahad et al 2015) and may be involved in increasing resistance to biotic stresses by inducing the systemic resistance process (Nakashita et al 2003). At high temperatures, brassinosteroids also affect the plant's carbohydrate metabolism and photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the EBR application exerts a direct role in the regulation of plant photosynthesis [ 2 ]. Several studies have also reported the role of EBR in the protection of photosynthetic apparatus against environmental stresses by enhancing plant tolerance to abiotic stresses [ 1,[3][4][5] ]. Brassinosteroid-enhanced stress tolerance was proposed to relate to increased activity of the reactive oxygen species scavenging system -antioxidant enzymes (via accumulation of abscisic acid) and with increased content of ascorbic acid and carotenoids [ 1,3,5 ].…”
mentioning
confidence: 99%
“…In plants of the Poaceae family, BRs have been found so far in rice (Oryza sativa) (Abe et al 1984(Abe et al , 1995Park et al 1994;Suzuki et al 1995;Wu et al 2008;Asahina et al 2014), maize (Zea mays) (Gamoh et al 1990;Suzuki et al 1986;Kim et al 2005), wheat (Triticum aestivum) (Yokota et al 1994;Janeczko and Swaczynova 2010), rye (Secale cereale) (Schmidt et al 1995;Antonchick et al 2003Antonchick et al , 2005, barley (Janeczko et al 2011;Dockter et al 2014) as well as in canary grass (Phalaris canariensis) (Shimada et al 1996) and perennial ryegrass (Lolium perenne) (Taylor et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…BL, CS in cv. Sezam (Janeczko et al 2011); CS, EBL and 28-homocastasterone (HCS) in cv. Bowman (Dockter et al 2014;Gruszka et al 2016a); CS in cv.…”
Section: Discussionmentioning
confidence: 99%